THE PLACE OF SOCIAL AND MORAL VALUES IN THE HIGH SCHOOL CURRICULUM FROM THE REPUBLIC OF MOLDOVA - Lungu, Viorelia; Cretu, Liliana; Munteanu, Tamarea; Sadovei, Larisa (LPPM Universitas Jambi, 2025)
This study examines how social and moral principles are included into the Republic of Moldova’s high school curriculum and offers methods for doing so successfully. The study finds the global trend of emphasizing character education to promote proactive citizenship through secondary analysis of previous studies. The Education Code of Moldova delineates social and moral norms that correspond with Western educational frameworks, such those in the United States, Germany, and the Netherlands, which serve as standards for Moldova’s educational system. However, there are also obstacles in the way of properly putting these ideals into practice, such as a lack of pedagogical topic understanding and parental and school administrator support for teachers to act as role models. The study offers a number of solutions to these obstacles, such as small group exercises, class discussions, and problem-centered learning. Furthermore, their inclusion in the curriculum can be strengthened by incorporating moral and social ideals into certain courses like drama, social studies, and music. The study comes to the conclusion that although incorporating moral and social values into Moldova’s educational system is important, specific tactics and increased assistance for teachers are required to get past current barriers and guarantee that the values are successfully taught to pupils.